2022
DOI: 10.1002/chem.202202798
|View full text |Cite
|
Sign up to set email alerts
|

Going Viral: An Investigation into the Chameleonic Behaviour of Antiviral Compounds

Abstract: The ability to adjust conformations in response to the polarity of the environment, i.e. molecular chameleonicity, is considered to be important for conferring both high aqueous solubility and high cell permeability to drugs in chemical space beyond Lipinski's rule of 5. We determined the conformational ensembles populated by the antiviral drugs asunaprevir, simeprevir, atazanavir and daclatasvir in polar (DMSO-d 6 ) and non-polar (chloroform) environments with NMR spectroscopy. Daclatasvir was fairly rigid, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“… The binding-site of NS3/4a is rather shallow and flat, making it difficult to target, and at the same time explains the open and flat conformation attained by simeprevir in this structure. Simeprevir has also been studied in solution; NMR ensembles in DMSO and chloroform revealed at least 15 different conformations, again demonstrating the flexibility span and gives an indication as to why it is so difficult to obtain crystals . Similar to pacritinib, the 0.85 Å MicroED structure of simeprevir (Figure ) displays two conformations in the asymmetric unit (Figure SI-4a).…”
Section: Resultsmentioning
confidence: 94%
“… The binding-site of NS3/4a is rather shallow and flat, making it difficult to target, and at the same time explains the open and flat conformation attained by simeprevir in this structure. Simeprevir has also been studied in solution; NMR ensembles in DMSO and chloroform revealed at least 15 different conformations, again demonstrating the flexibility span and gives an indication as to why it is so difficult to obtain crystals . Similar to pacritinib, the 0.85 Å MicroED structure of simeprevir (Figure ) displays two conformations in the asymmetric unit (Figure SI-4a).…”
Section: Resultsmentioning
confidence: 94%
“…However, the majority of the oral macrocycles reside far into the bRo5 chemical space for several descriptors, i.e., MW, TPSA, and HBA. It is often assumed that compounds in the bRo5 space may achieve satisfactory cell permeability and solubility by behaving as molecular chameleons that adapt their conformations to the surrounding environment. , Experimental support for chameleonic behavior has been reported for several macrocyclic drugs in the bRo5 space, with cyclosporin being studied extensively and others such as roxithromycin, telithromycin, spiramycin, and simeprevir being investigated recently. ,, …”
Section: Resultsmentioning
confidence: 99%
“… 25 , 21 Experimental support for chameleonic behavior has been reported for several macrocyclic drugs in the bRo5 space, with cyclosporin being studied extensively and others such as roxithromycin, telithromycin, spiramycin, and simeprevir being investigated recently. 26 , 24 , 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, NMR showed that the orientation of the side chains of telithromycin and roxithromycin varied between nonpolar and polar environments, confirming the crucial effect of macrocyclic side chains on chameleonicity . Recently, the same method has also been applied to PROTACs and nonmacrocyclic compounds (antivirals) . This approach has the advantage of focusing on true solution conformers, but it mainly remains a semiquantitative case-per-case investigation method.…”
Section: Introductionmentioning
confidence: 99%